Evaluating The Impact of ESG Integration on The Financial Performance of Pertamina Geothermal Energy: A Sustainable Growth Perspective - Tasya Ravida Ayu Padantya; Oktofa Yudha Sudrajad (PT. Publikasiku Academic Solution, 2024)
The global energy landscape is undergoing a significant transformation driven by the urgent need to mitigate climate change, increased regulatory pressures, and rising stakeholder expectations. This study aims to explore the impact of ESG integration on the financial performance of Pertamina Geothermal Energy (PGE), a subsidiary of PT Pertamina (Persero), which plays an important role in the energy transition in Indonesia. This study uses secondary data from financial statements, prospectuses, annual reports, and information from the PGE website. In addition, historical data on the stock prices of power generation companies and comparative analysis of the industry are used. The analysis was carried out using the Discounted Cash Flow (DCF) method to calculate the intrinsic value of the company, as well as an assessment of sustainability policies, community engagement programs, and improvement of corporate governance. The results show that ESG integration has a positive impact on PGE's sales growth, profitability, and return on investment. Improved sustainability policies, community engagement programs, and corporate governance contribute significantly to better financial performance. The integration of ESG principles in PGE not only improves financial performance but also shows that sustainability and profitability can go hand in hand. These findings provide valuable insights for the broader energy sector, suggesting that ESG integration can drive positive change and facilitate an era where financial growth and environmental responsibility complement each other.